Sosialisasi Dan Penerapan HOTS Dalam Pembelajaran Berbasis Proyek Di SDN 12 Konda - Chairan Zibar L. Parisu; Erwin Eka Saputra; Kasmawati Kasmawati; La Sisi; Waode Ekadayanti (Prodi PGSD Unsultra, 2025)
21st century education requires students to have higher order thinking skills (HOTS) in order to compete in the era of globalization. However, the implementation of HOTS in Elementary Schools (SD) still faces various challenges, especially in the use of appropriate learning methods. This Community Service (PKM) activity aims to socialize the HOTS concept and its application in project-based learning to elementary school teachers. The methods used in this PKM include training, mentoring, and direct practice in compiling and implementing HOTS-based project-based learning. The results of the activity showed an increase in teachers' understanding of HOTS and its implementation in learning. In addition, students were also more active and creative in the learning process. This activity is expected to improve the quality of learning in elementary schools and support the development of 21st century skills for students.